Meningkatkan Kreativitas Pasien ODGJ (Orang Dengan Gangguan Jiwa) Di Yayasan Satu Hati Membangun - Shilcia Oktaviani; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Mental disorders are behavioral patterns shown in individuals that cause distress, reduce quality of life and dysfunction. Mental disorders also affect Some mental disorders that are quite common in the community include depression, anxiety/anxiety, schizophrenia, bipolar, PTSD, personality disorders, etc. Those who experience mental disorders will experience changes in their thoughts, feelings and behavior, so that it can interfere with work, daily activities and patterns of relationships with other people. One Heart to Empower Foundation (YASAM) is an institution engaged in Social, Education, and Humanitarian fields. YASAM's address is at Jalan Bunga Rampai IV, Simalingkar B, Kec. Profit Field. YASAM has 4 programs, one of which is social rehabilitation which deals with drug problems and mental health disorders. The services provided to patients are religious guidance, counseling with psychologists, assessment by social workers, music therapy, skills guidance, and recreation. On this occasion, the practitioner applies learning about self-creativity to one of the patients at YASAM.